Examining students’ level of understanding toward COVID-19 and its associated factors in Ethiopia: a systematic review and meta-analysis - Chereka, Alex Ayenew; Demsash, Addisalem Workie; Butta, Fikadu Wake; Shibabaw, Adamu Ambachew; Gebeyehu, Chernet Desalegn; Adane, Daniel; Limeneh, Wubalem Dilie; Fentahun, Amare Dagnew; Tadesse, Mathias Nega; Kitil, Gemeda Wakgari (Frontiers in Public Health, 2024)
Background This systematic review and meta-analysis aim to investigate students’ understanding of COVID-19 in Ethiopia and identify associated factors. The primary goal is to pinpoint key contributors shaping students’ perception and comprehension of the virus. The study aims to offer valuable insights for developing targeted educational interventions, ultimately enhancing students’ overall knowledge and awareness of the pandemic in the specific context of Ethiopia. Methods The study adhered rigorously to PRISMA criteria, ensuring a standardized methodology. Data from reputable databases like Google Scholar and PubMed were systematically collected. Ten relevant articles were meticulously analyzed using STATA version 11, with heterogeneity assessed by the I2 test. A funnel plot and Egger’s test were used to check for publication bias. The determination of the pooled effect size utilized a random-effect model meta-analysis, offering a robust 95% confidence interval. Results This meta-analysis, based on 10 articles, reveals an overall prevalence of 61.58% (95% CI: 47.26–75.89). Significant contributors to students’ comprehension include Social media users (AOR) = 2.38, urban residence AOR = 3.31, news media followers AOR = 2.51, fathers’ educational status AOR = 2.35, watching television AOR = 4.71, and health science students AOR = 4.21. These findings underscore crucial elements shaping students’ understanding of COVID-19 in Ethiopia. Conclusion Our analysis indicates that 61.58% of Ethiopian students possess a good understanding of COVID-19. Factors such as active social media engagement, geographic location, frequency of news consumption, father’s level of education, television viewing habits, and enrollment in health science programs significantly influence their comprehension. These findings underscore the importance of implementing targeted interventions to enhance health literacy and education among students, thereby facilitating a more effective response to pandemics.